Ecobricks And Ecopreneurship as Effort Plastic Waste Management In The Kampung Wisata Warna Warni Jodipan, Malang City: Ecobricks Dan Ecopreneurship Sebagai Upaya Pengelolaan Sampah Plastik Di Kampung Wisata Warna Warni Jodipan Kota Malang - Parmawati, Rita; Fadli, Moh.; Semedi, Bambang; Handawijaya, Gala Kurnia (LPPM Universitas Yudharta Pasuruan, 2022)
The objective of this program is managing tourism plastic waste into creative economic products and gaining community empowerment by Community Partnership Program. A community assistance team collaborate with Kampung Warna Warni Jodipan Malang City deciced Ecobrick as the method to creating plasti waste economic products in order to gaining community income as the support for successing sustainable tourism village. Three stages provided for community development, included (1) providing education to the community regarding Sustainable Waste Management Ecobrick and Ecopreneurship as the waste utilization program; (2) informing to the participant about plastic waste hazards to the environment; (3) providing training to the participant about preparation and manufacturing of Ecobricks and Ecopreneurship. The outcomes of this program are participants can understand the concept Sustainable Waste Management, Ecobrick and Ecopreneurship; mindset transformation about the urgency of plastic waste management and environmental protection act, understand the process of ecobrick and ecopreneurship products, also to understand the added value from waste management that can be used as livelihood alternative.